2019
DOI: 10.48550/arxiv.1901.06482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Efficient Optimal Transport: An Analysis of Greedy and Accelerated Mirror Descent Algorithms

Tianyi Lin,
Nhat Ho,
Michael I. Jordan

Abstract: We provide theoretical analyses for two algorithms that solve the regularized optimal transport (OT) problem between two discrete probability measures with at most n atoms. We show that a greedy variant of the classical Sinkhorn algorithm, known as the Greenkhorn algorithm, can be improved to O n 2 ε 2 , improving on the best known complexity bound of O n 2 ε 3 . Notably, this matches the best known complexity bound for the Sinkhorn algorithm and helps explain why the Greenkhorn algorithm can outperform the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…We introduce a novel accelerated primal-dual randomized coordinate descent (APDRCD) algorithm for solving the OT problem. We provide a complexity upper bound of O( n 5/2 ε ) for the APDRCD algorithm, which is comparable to the complexity of state-of-art primal-dual algorithms for OT problems, such as the APDAGD and APDAMD algorithms [8,16]. To the best of our knowledge, this is the first accelerated primal-dual coordinate descent algorithm for computing the OT problem.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…We introduce a novel accelerated primal-dual randomized coordinate descent (APDRCD) algorithm for solving the OT problem. We provide a complexity upper bound of O( n 5/2 ε ) for the APDRCD algorithm, which is comparable to the complexity of state-of-art primal-dual algorithms for OT problems, such as the APDAGD and APDAMD algorithms [8,16]. To the best of our knowledge, this is the first accelerated primal-dual coordinate descent algorithm for computing the OT problem.…”
Section: Introductionmentioning
confidence: 93%
“…Several algorithms have been proposed to circumvent the scalability issue of the interior-point methods, including the Sinkhorn algorithm [5,12,14,24], which has a complexity bound of O( n 2 ε 2 ) where ε > 0 is the desired accuracy [8]. The Greenkhorn algorithm [1] further improves the performance of the Sinkhorn algorithm, with a theoretical complexity of O( n 2 ε 2 ) [16]. However, for large-scale applications of the OT problem, particularly in randomized and asynchronous scenarios such as computational Wasserstein barycenters, existing literature has shown that neither the Sinkhorn algorithm nor the Greenkhorn algorithm are sufficiently scalable and flexible [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Algorithmic approaches in specific application settings include portfolio selection [5], covariance estimation [29], Kalman filtering [1], dynamic control [46,47], hypothesis testing [20] and traveling salesman problems [12]. These algorithmic advances in DRO are accompanied by significant progress in computational optimal transport (see [33,6,25] and references therein).…”
Section: Introductionmentioning
confidence: 99%